SISTEM INFORMASI MANAJEMEN PERKARA DI PENGADILAN NEGERI KRAKSAAN BERBASIS WEB - Husnul Hotimah; Andi Wijaya; Zainal Arifin (SENTIA 2016, 2016)
Case is an action that often occurs in the community wheater it is a criminal cases (drugs, harrasment, murderer, etc) and civil cases of abuse (divorce, in herintance, etc). Case management starting from the reporting, complaint, or the registration of the legal services to the execution phase and correctional decision is an integral process of the start of the legal events in the community until the establishment of a state or recoverable back justice in socienty. So that the district court on duty and autorized to investigate, adjudicate and resolve criminal cases and civil cases and the first level. Methods used in the making of this information system is the observation by coming directly to the district court kraksaan, conduct interviews on the parties and collected data arrives related to case management. The purpose of the development of case management information system is to provide easy to get the information in a case. The advantages of this system is the ease of finding a case of data. The weakness of the system not complete all the data stored in the base case data and performance has not been tested with good system.